2012
DOI: 10.1002/jcb.24002
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Radioresistant Osteosarcoma Cells With Parthenolide

Abstract: Osteosarcoma is a devastating tumor of bone, primarily affecting adolescents. Osteosarcoma tumors are notoriously radioresistant. Radioresistant cancers, including osteosarcoma, typically exhibit a considerable potential for relapse and development of metastases following treatment. Relapse and metastatic potential can, in part, be due to a specific radioresistant subpopulation of cells with stem-like characteristics, cancer stem cells, which maintain the capacity to regenerate entire tumors. In the current st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 52 publications
2
36
0
Order By: Relevance
“…The current study has shown that PN could affect both bulk and melanoma stem-like cells. It supports previously published reports describing similar activity of PN in other cancers 26 , 27 , 38 . Importantly, PN has already shown safety in Phase I/II clinical trials 39 , 40 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The current study has shown that PN could affect both bulk and melanoma stem-like cells. It supports previously published reports describing similar activity of PN in other cancers 26 , 27 , 38 . Importantly, PN has already shown safety in Phase I/II clinical trials 39 , 40 .…”
Section: Discussionsupporting
confidence: 91%
“…PN decreased the viability of prostate tumor-initiating cells isolated from cell lines and from patients, and inhibited prostate cancer stem-cell-mediated tumor initiation and progression in mouse xenografts 25 . Recently, it has been shown that the combination of PN and inhibitors of the PI3K/mTOR pathway synergized to eradicate both bulk and stem cell populations of AML, 26 and the combination of PN with ionizing radiation significantly reduced the viability of both the overall population of osteosarcoma cells and the cancer stem cell subpopulation 27 . On the basis of all these findings, it was tempting to speculate that PN would be able to affect melanoma stem-like cells.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is consistent despite accounting for EOD and other variables such as tumor size and age in our multivariate model, and furthermore, when doing separate analyses for patients diagnosed after 1990 to account for contemporary improvements in radiotherapy technology over time. OGS is notoriously radioresistant [29,30]; thus, radiotherapy is likely not a good therapy in the treatment of OGS in the spine unless used for palliative purposes or as a last resort. Indeed, we acknowledge the high likelihood of confounding bias here, wherein clinicians treating patients in the present study cohort are more likely to use radiotherapy in patients with advanced OGS of the spine.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, parthenolide appears to synergically enhance chemotherapeutic efficiency when it is combined with taxol or cisplatin to treat lung and gastric cancer cells (23, 40). Parthenolide also sensitizes radioresistant osteosarcoma cells to radiotherapy (41). Here, we demonstrate that DMAPT, a parthenolide prodrug, sensitized prostate cancer cells to radiotherapy in vivo and protected normal prostate and bladder against radiation-induced tissue injury.…”
Section: Discussionmentioning
confidence: 99%